Emerging drugs for the treatment of HIV/AIDS: a review of 2019/2020 phase II and III trials. (3rd July 2021) - Piscaglia, Marco; Cossu, Maria Vittoria; Passerini, Matteo; Petri, Francesco; Gerbi, Martina; Fusetti, Chiara; Capetti, Amedeo; Rizzardini, Giuliano
ABSTRACT: Introduction: The study of emerging drug trials to treat people living with HIV (PLWH) helps to understand any advantages and disadvantages of therapies that will be available on the market in the short-term future as well as the mechanisms underlying a better cure. Areas covered: This review analyzes phase 2 and 3 clinical trials published between 2019 and 2020 concerning six different emerging drugs. The majority of the trials focus on long acting drugs, but also on new orally administered compounds. Expert opinion: The biggest news in antiretroviral therapy (ART) is the approval of cabotegravir/rilpivirine as a complete long-acting (LA) therapeutic regimen. It paves the way for an innovation that may change the paradigms of HIV treatment in the long term, albeit it will not be obvious to implement and treatment adherence still needs to be fully evaluated. Results of phase 3 Islatravir trials are awaited. Lenacapavir may soon reach phase 3. These drugs may pave the way for 6-month ART in the next future. Fostemsavir has been recently approved. Albuvirtide, a fusion inhibitor approved in China, presents several limitations for its intravenous use only. UB-421 and VRC01 are monoclonal antibodies against HIV. This emerging technology has shown interesting results but needs further studies.